2011
DOI: 10.1159/000326915
|View full text |Cite
|
Sign up to set email alerts
|

3,5-Dimethyl-<sup>7</sup>H-Furo[3,2-g]Chromen-7-One as a Potential Anticancer Drug by Inducing p53-Dependent Apoptosis in Human Hepatoma HepG2 Cells

Abstract: Background/Aims: Coumarins are natural compounds found in many plants that possess medical value by itself and its modified derivatives. Method: Six novel coumarin derivatives were synthesized and examined for their potential anticancer cytotoxicity. Result: Among the 6 derivatives, 3,5-dimethyl-7H-furo[3,2-g]chromen-7-one (DMFC) presented the strongest cytotoxicity against human hepatoma HepG2 cells in vitro with an IC50 value of 8.46 ± 0.28 µM in a 48-hour treatment. Further experiments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 72 publications
0
18
0
Order By: Relevance
“…In particular, NF-κB appears to be responsible for the activation of genes involved in proliferation and tumor survival, such as those of the apoptotic proteins Bcl-2 and Bcl-xL (50,51). The results of the present study indicated that PT is essential for AOM/DSS-induced colon cancer carcinogenesis via the apoptotic route-associated Bcl-2 family members, which cause inhibition of NF-κB activation.…”
Section: Discussionmentioning
confidence: 52%
“…In particular, NF-κB appears to be responsible for the activation of genes involved in proliferation and tumor survival, such as those of the apoptotic proteins Bcl-2 and Bcl-xL (50,51). The results of the present study indicated that PT is essential for AOM/DSS-induced colon cancer carcinogenesis via the apoptotic route-associated Bcl-2 family members, which cause inhibition of NF-κB activation.…”
Section: Discussionmentioning
confidence: 52%
“…On the other hand, it is well known that NF-кB is responsible for the activation of genes involved in proliferation and tumor survival, such as the apoptotic proteins Bcl-2 and Bcl-XL [61,62]. In fact, this transcription factor has been found to be overactivated in many tumors [63-65].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, 5 patients had severe myelotoxicity which necessitated a reduction in the number of cycles [12]. In a study by Martin et al [13], 400 mg/m 2 carboplatin was administered to 34 untreated patients with MBC every 4 weeks. The RR was 35% (1 CR and 11 PRs).…”
Section: Experience With Single-agent Therapymentioning
confidence: 99%
“…Toxicities were mild and included thrombocytopenia, leukopenia and nausea/vomiting. Only 1 patient developed grade IV thrombocytopenia without overt bleeding [13]. Another study enrolled 40 patients with MBC (13 previously treated and 27 untreated patients) to receive carboplatin doses adjusted for glomerular filtration rate using the Calvert formula.…”
Section: Experience With Single-agent Therapymentioning
confidence: 99%